2015
DOI: 10.4103/0974-2069.149512
|View full text |Cite
|
Sign up to set email alerts
|

e-Teaching in pediatric cardiology: A paradigm shift

Abstract: Background:Training of postgraduate students has traditionally been done in person in a hospital setting with hands-on training with each faculty member imparting knowledge to 2 to 4 students per year. Supplementing their practical education with online instruction could make a significant difference in standardizing pediatric cardiology education in India.Objective:To present the rationale, methods and survey results of a live e-Teaching methodology implemented for Pediatric cardiology trainees in association… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 2 publications
0
11
0
Order By: Relevance
“…However, in spite of its multiple advantages there are quite a few limitations of e-learning such as social isolation, lack of studentteacher interaction and connectivity issues etc. [7][8][9] Despite the wide-based adoption of e-learning the world over, it was never considered as a part of formal education in Pakistan by majority of the institutions until the spread of Covid-19 recently. 9,10 Due to the lockdown situation however, now a lot of schools, colleges and even undergraduate medical and dental institutes across the country are moving towards e-learning.…”
Section: Original Articlementioning
confidence: 99%
See 2 more Smart Citations
“…However, in spite of its multiple advantages there are quite a few limitations of e-learning such as social isolation, lack of studentteacher interaction and connectivity issues etc. [7][8][9] Despite the wide-based adoption of e-learning the world over, it was never considered as a part of formal education in Pakistan by majority of the institutions until the spread of Covid-19 recently. 9,10 Due to the lockdown situation however, now a lot of schools, colleges and even undergraduate medical and dental institutes across the country are moving towards e-learning.…”
Section: Original Articlementioning
confidence: 99%
“…so that continued education can be provided without getting much affected during the quarantine period. 7,8,11 Also various e-teaching softwares are being explored by teachers to bring maximum possible ease for their students.…”
Section: Original Articlementioning
confidence: 99%
See 1 more Smart Citation
“…Students can take their online courses anytime and anywhere, enabling them to become lifelong learners [ 10 ]. Nevertheless, e-learning has few drawbacks, like social isolation, lack of communication and interaction, and network problems [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…This is especially true regarding specialty and sub-specialty education. 6,7 These barriers often have identifiable solutions. 8 For instance, even in areas with limited access to computers and poor physical infrastructure, a break-even cost analysis by Maloney and colleagues 9 found that the web-based approach to learning was superior to the traditional face-to-face education.…”
mentioning
confidence: 99%